Desulphurization of model oil and diesel using ionic liquid - Mohd Rafiqul Zarin, Ramli (2014)
Diesel is a multi-purpose petroleum fuel used in all kinds of vehicles. But remains one of the largest source of fine particle air pollution, which has serious health impacts. Depending on the crude oil used and the refinery configurations, sulphur levels in diesel range from below 10 ppm to as high as 1000 ppm. In fact, Europe, United States, and Japan have all put in place measures to reduce sulphur to lower levels which is below 10 ppm to 15 ppm, often along with emission standards that require advanced emission control technologies that cannot be used with higher sulphur fuels. By March of 2008, there are many countries that have switched to diesel fuel with 500 ppm or less such as Philippines, Singapore, and Thailand including our country, Malaysia. There are various methods applied in industry to obtain low-sulphur fuels such as hydrocracking processes. But, the sulphur removal using ionic liquids are gaining wide recognition as potential environmental solvents due to their very low vapour pressure, their thermal and chemical stability, their ability to act as a catalyst, and their non-flammability and non-corrosive properties. The procedures include with three sub-process which first (ILs) is analyse with Fourier transform infrared spectroscopy (FTIR). The liquid was placed on a Germanium (Ge) plate by using a dropper and the test is run until a constant reading is visible. It is then followed by a wavelength classification by referring it to a table of characteristic IR absorptions. From the classification, it was found that there is a trace of functional groups consists of amines, amides, aromatics and alkyl halides. The lower frequency, 874.55 cm-1 and 777.29 cm-1 have functional group of aromatics with bond C-H "oop". The highest frequency with 3421.96 cm-1 has functional group of 1o, 2o amines or amides with bond N-H Stretch. Besides, there are also components with functional group of aliphatic amines with bond C-N Stretch at frequency 1044.97 cm-1 and 1104.56 cm-1 respectively. Other than that, there is functional group of alkyl halides with bond C-H wag (CH2X) at frequency 1179.15 cm-1. Secondly, the ionic liquid was undergone a CHNOS testing to check the percentage of carbon (C), Nitrogen (N), Oxygen (O), and Sulphur (S) that presented within ionic liquids. The ionic liquid was sent to University Malaysia Pahang (UMP) Central Laboratory to obtain the results. Based on the result obtained, the (ILs) consists of Nitrogen by 11.37%, Carbon by 15.84%, Hydrogen by 6.729%, Sulphur by 11.185% and rest of the composition is for Oxygen by 15.84%. The result will be compared theoretically with the structure formula of (ILs)